Existence and generic stability of solutions for multiclass multicriteria traffic equilibrium problems with capacity constraints of arcs. (2nd November 2019) - Lin, Zhi; Zhou, Daqiong; Peng, Zaiyun; Wang, Jingjing
ABSTRACT: In this paper, we introduce the multiclass multicriteria traffic equilibrium problem with capacity constraints of arcs and its equilibrium principle. Using Fan–Browder's fixed points theorem and Fort's lemma to prove the existence and generic stability results of multiclass multicriteria traffic equilibrium flows with capacity constraints of arcs.